Investigation of food waste valorization through sequential lactic acid fermentative production and anaerobic digestion of fermentation residues. (October 2017) - Demichelis, Francesca; Pleissner, Daniel; Fiore, Silvia; Mariano, Silvia; Navarro Gutiérrez, Ivette Michelle; Schneider, Roland; Venus, Joachim
Graphical abstract: Highlights: New concept of cascadic use of food waste was investigated. SHF and SSF approaches for LA have been executed. Yield and productivity were slightly higher for SHF compared to SSF. Integration of biogas production from fermentative residues. Preliminary economic and environmental assessment of the proposed two-step biorefinery process. Abstract: This work concerns the investigation of the sequential production of lactic acid (LA) and biogas from food waste (FW). LA was produced from FW using a Streptococcus sp. strain via simultaneous saccharification and fermentation (SSF) and separate enzymatic hydrolysis and fermentation (SHF). Via SHF a yield of 0.33 gLA /gFW (productivity 3.38 gLA /L·h) and via SSF 0.29 gLA /gFW (productivity 2.08 gLA /L·h) was obtained. Fermentation residues and FW underwent anaerobic digestion (3 wt% TS). Biogas yields were 0.71, 0.74 and 0.90 Nm 3 /kgVS for FW and residues from SSF and SHF respectively. The innovation of the approach is considering the conversion of FW into two different products through a biorefinery concept, therefore making economically feasible LA production and valorising its fermentative residues. Finally, a mass balance of three different outlines with the aim to assess the amount of LA and biogas that may be generated within different scenarios is presented.